(untitled) (Research, Society and Development, 2021)
The treatment of teeth affected by periodontal diseases has been shown efficient in keeping them in the oral cavity or as support for fixed prosthesis for long periods, showing around a 90% survival rate. However, regarding the inter-relation of Periodontics and Implantology, recent research has shown that the number of extractions of teeth damaged by the periodontal disease has been increasing significantly. In addition to caries and periodontal disease, the dentists’ forceps action is one of the main causes of extraction, which is used in the most varied situations and usually following the professionals’ own criteria. The implantology advance and the appearance of implant industries changed several aspects of the prognosis regarding keeping the teeth (or not). Periodontics is discipline that seek to develop methodologies and clinical decisions based on scientific evidence and on ethics prognosis that really favor the patients. This study aims at contributing to this debate and presents clinical cases in which periodontal damaged teeth were not referred to extraction and were preserved and kept in the oral cavity.